Characterization of Interface and Bulk Traps in Ultrathin Atomic Layer-Deposited Oxide Semiconductor MOS Capacitors With HfO2/In2O3 Gate Stack by C-V and Conductance Method - Wang, Ziheng; Lin, Zehao; Si, Mengwei; Ye, Peide D. (Frontiers in Materials, 2022)
Oxide semiconductors have attracted revived interest for complementary metal–oxide–semiconductor (CMOS) back-end-of-line (BEOL) compatible devices for monolithic 3-dimensional (3D) integration. To obtain a high-quality oxide/semiconductor interface and bulk semiconductor, it is critical to enhance the performance of oxide semiconductor transistors. Atomic layer-deposited (ALD) indium oxide (In2O3) has been reported with superior performance such as high drive current, high mobility, steep subthreshold slope, and ultrathin channel. In this work, the interface and bulk traps in the MOS gate stack of ALD In2O3 transistors are systematically studied by using the C–V and conductance method. A low EOT of 0.93 nm is achieved directly from the accumulation capacitance in C–V measurement, indicating a high-quality gate oxide and oxide/semiconductor interface. Defects in bulk In2O3 with energy levels in the subgap are confirmed to be responsible for the conductance peak in GP/ω versus ω curves by TCAD simulation of C–V and G–V characteristics. A high n-type doping of 1×1020/cm3 is extracted from C–V measurement. A high subgap density of states (DOS) of 3.3×1020 cm−3 eV−1 is achieved using the conductance method, which contributes to the high n-type doping and high electron density. The high n-type doping further confirms the capability of channel thickness scaling because the charge neutrality level aligns deeply inside the conduction band.